Depiction of Narasimha killing the demon Hiranyakashipu - Temples of India Project Team (Jio Institute, 2024)
The bhadra (central projection) has a depiction of Narasimha killing the demon, Hiranyakashipu. The recesses have vyala and mithuna/maithuna figures.